Harald Motzki's Method of Perspective Hadith Authenticity and His Response to Orientalist Skepticism of Hadith - Muhammad Ilham Baihaqqi; Nur Kholis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article aims to describe the method used by Harald Motzki in exploring the authenticity of hadith and to describe his refutation of Orientalist skepticism towards hadith. Since the 19th century scientifically, orientalists began to study the authenticity of hadith as a source of Islamic teachings, the skeptical attitude of some orientalists was challenged by Muslim thinkers and several other orientalists. For Motzki, both camps have not answered the substance of the question of the authenticity of the hadith itself, he also uses certain methods in answering this. This type of research is qualitative with a descriptive-analytical method. This paper aims to reveal Harald Motzki's hadith methodology and forms of criticism of the thoughts of Orientalist figures systematically, so that readers can understand the sensitive points in hadith studies that are the target of Orientalist criticism and how to respond to them. . The results show that Motzki succeeded in proving that the Prophet's hadith can be traced back to the first century Hijriah using Musannaf 'Abd al-Razzaq as a sample. Then, Harald Motzki succeeded in breaking the theories of his predecessors with the theory of dating and isnad cum matn. He counterattacked criticism of the sanad of Ignaz Goldziher and Joseph Schacht, criticism of the common link and gold isnad of G.H.A. Juynboll. Apart from that, the contribution he made became a spark for the birth of scientific studies on hadith in the future. For example, the isnad cum matn theory is often used to identify the quality of a hadith to this day.